2019
DOI: 10.12968/ijtr.2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Muscle Energy Techniques versus cross (X) technique kinesio taping to treat chronic low back dysfunction

Abstract: Background/Aims: Chronic low back dysfunction is a serious health problem affecting people at some time in their life; it impedes the mobility of the lumbar spine and adjacent joints leading to functional disabilities. Muscle Energy Techniques aim to normalise soft tissue structures, such as shortened or tight muscles, with no direct implication to the joint associated with these soft tissues. Kinesio taping supports damaged structures without restriction of mobility and at the same time may influence some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The same application was made on the other side of the spine. Finally, the third patch was applied transversely to the rst two with a tension correction of 70-80% using the musculoskeletal method, then the bases of the patch were glued on both sides without generating tension [25,26].…”
Section: Interventionsmentioning
confidence: 99%
“…The same application was made on the other side of the spine. Finally, the third patch was applied transversely to the rst two with a tension correction of 70-80% using the musculoskeletal method, then the bases of the patch were glued on both sides without generating tension [25,26].…”
Section: Interventionsmentioning
confidence: 99%
“…There were twenty-three RCTs related to conditions of the lumbar spine and abdominal wall, with all but one assessing KT (Appendix 2 File: Appendix 2G). One addressed KT for acute low back pain [136], two investigated KT for back pain in the setting of lumbar disc herniation [137,138], two investigated KT for pregnancy related low back pain [139,140], one RCT investigated postpartum diastasis recti abdominis [141], and sixteen investigated KT for chronic low back pain, [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157]. One study evaluated rigid taping for sacroiliac joint dysfunction [158].…”
Section: Lumbar Spinementioning
confidence: 99%
“…It can be used to improve joint mobility by influencing the dysfunctional soft tissues and to relax tight tens musculature, spasms, or fibrotic changes. It can help increasing muscle strength, increasing range of motion (ROM) and decreasing edema (Elshinnawy et al, 2019). Although the limited number of high quality studies available to reach conclusive opinion (Franke et al, 2015), MET has been shown to be effective in reducing pain (Phadke et al, 2016), improving ROM, and functional level (Patel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%